Understanding on-line community: the affordances of virtual space - Karen Ruhleder (Information Research: An International Electronic Journal)
Increasing numbers of on-line venues for learning are emerging as virtual communities become more accessible and commonplace. This paper looks at one particular virtual community, an on-line degree programme at the University of Illinois, Urbana-Champaign, which offers an M.S. in Library and Information Science (called LEEP). It draws on a framework presented by Mynatt, et al. (1998), which provides a lens for talking about on-line community as a set of affordances. This framework is applied to illustrate the interactions, artefacts, and expectations that shape this community.